Computer-aided Simulation of a Cascade Biorefinery: Case Study of the Colombian Amazon’s Hass Avocado Waste - Anibal Alviz-Meza; Stefany A. Valdez-Valdes; Angel D. Gonzalez-Delgado (Chemical Engineering Transactions, 2025)
Colombia has established itself as a significant contributor to Hass avocado production; however, the supply chain predominantly focuses on marketing the pulp, thereby underutilizing by-products, such as the seed. This situation presents environmental challenges and overlooks potential economic opportunities within bioeconomy development. This study introduces a cascade biorefinery model designed to valorize avocado seed waste from Colombia's Amazon region, transforming it into high-value products, including starch and biodegradable biofilms. The methodology employed involves process simulation using Aspen Plus, with NRTL models for the liquid phase and the Redlich-Kwong model for the vapor phase, to model separation and reaction stages accurately. The biorefinery comprises three principal modules: (i) pretreatment and wet extraction, which produces 1.92 kg/h of starch comparable in composition to commercial avocado seed flours; (ii) a starch gelatinization process with glycerol, yielding 3.76 kg/h of type 1 biofilm; and (iii) a thermochemical and biotechnological process encompassing acid hydrolysis, lactic acid fermentation, and polymerization, resulting in polylactic acid. This PLA is subsequently combined with starch to generate 3.44 kg/h of type 2 biofilm. The entire process attains a 78.34% yield based on a waste input of 27.4 kg/h, thereby demonstrating efficient biomass recovery. The principal contribution of this research lies in showing, through detailed simulation, the technical feasibility of a multistep system that integrates physical, chemical, and biotechnological processes to produce functional bioproducts from agricultural waste. Unlike fragmented approaches, this cascade biorefinery optimizes resource utilization, broadens product diversity, and minimizes waste, thereby supporting sustainability and circular economy principles.